2020
DOI: 10.3390/molecules25122745
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in the Production and Applications of Ellagic Acid and Its Derivatives. A Review

Abstract: Ellagitannins (ETs), characterized by their diversity and chemical complexity, belong to the class of hydrolysable tannins that, via hydrolysis under acidic or alkaline conditions, can yield ellagic acid (EA). They are mostly found as a part of extractives in angiosperms. As known antioxidants and chelators, EA and EA derivatives are drawing an increasing interest towards extensive technical and biomedical applications. The latter ones include possible antibacterial, antifungal, antiviral, anti-inflammatory, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
83
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(86 citation statements)
references
References 136 publications
(171 reference statements)
1
83
0
2
Order By: Relevance
“… 22 ETs are hydrolyzed in the gut to release ellagic acid (EA), which is further processed by the microflora into urolithins through the loss of one of its two lactones and by successive removal of hydroxyl groups. 23 In the species investigated to date (including humans), urolithin A (UA), urolithin B (UB), urolithin C (UC) and urolithin D (UD) are the redundant measurable metabolites that are considered to be the end-products of both ETs and EA. 24 Many studies suggest that urolithin A (UA) is the main functional substance in antioxidant and anti-inflammatory activities after the body consumes foods rich in ellagitannin or ellagic acid.…”
Section: Introductionmentioning
confidence: 99%
“… 22 ETs are hydrolyzed in the gut to release ellagic acid (EA), which is further processed by the microflora into urolithins through the loss of one of its two lactones and by successive removal of hydroxyl groups. 23 In the species investigated to date (including humans), urolithin A (UA), urolithin B (UB), urolithin C (UC) and urolithin D (UD) are the redundant measurable metabolites that are considered to be the end-products of both ETs and EA. 24 Many studies suggest that urolithin A (UA) is the main functional substance in antioxidant and anti-inflammatory activities after the body consumes foods rich in ellagitannin or ellagic acid.…”
Section: Introductionmentioning
confidence: 99%
“…Berry juices significantly enhance the growth of acrylamide-exposed yeast cells, and decreased the level of ROS [14]. Ellagic acid (EA) as a plant-derived natural product found in pomegranate (Punica granatum) and the family of ellagitannins (ETs) has different pharmacological effects [15]. Ellagic acid has generated a noticeable scientific interest because of beneficial health effects against many oxidative-linked diseases, including neurodegenerative and cancer diseases [15].…”
Section: Introductionmentioning
confidence: 99%
“…Ellagic acid (EA) as a plant-derived natural product found in pomegranate (Punica granatum) and the family of ellagitannins (ETs) has different pharmacological effects [15]. Ellagic acid has generated a noticeable scientific interest because of beneficial health effects against many oxidative-linked diseases, including neurodegenerative and cancer diseases [15]. It has been reported that ellagic acid can prevent of oxidative stress, inflammation, and histopathological alterations in acrylamide-induced hepatotoxicity in wistar rats [16].…”
Section: Introductionmentioning
confidence: 99%
“…Herein, we also explored whether ellagic acid (EA), as a natural antioxidant polyphenol, served as a potential therapeutic drug to attenuate SCH‐induced abnormal glucose metabolism in mice. EA is a dimeric derivative of gallic acid and extensively excavated in natural nutriments (Evtyugin & Magina, 2020). Numerous evidence indicate that EA is a super bioactive molecule to perform multiple biomedical applications, including anti‐inflammatory, antibacterial, anti‐oxidative, and anticancer activities (Alfei et al., 2020; Baradaran Rahimi et al., 2020; Evtyugin & Magina, 2020).…”
Section: Introductionmentioning
confidence: 99%